2019
DOI: 10.1080/21691401.2019.1621328
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long noncoding RNA SNHG15 enhances the development of colorectal carcinoma via functioning as a ceRNA through miR-141/SIRT1/Wnt/β-catenin axis

Abstract: Colon cancer, also known as colorectal carcinoma (CRC), remains to be one of the most mainsprings of cancer-produced deaths entire world. We planned to grab the role and possible biological cause of a long noncoding RNA, namely, small nucleolar RNA host gene 15 (SNHG15), in CRC. The mRNA level of SNHG15 in CRC tissues and cells was detected, followed by investigating the impacts of the depression of SNHG15 on CRC cell proliferation (viability and colony-forming), apoptosis, migration, and invasion. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…SNHG15 is involved in colorectal cancer cell proliferation and migration via miR-141 (159) and miR-338-3p sponging (160), along with up-regulation of AIF (Allograft Inflammatory Factor 1) (152), and activation of transcription factor SLUG (45). In thyroid cancer, SNHG15 is a ceRNA for miR-510-5p (161) and miR-200a-3p (162).…”
Section: Small Nucleolar Rna Host Gene 15 (Snhg15)mentioning
confidence: 99%
“…SNHG15 is involved in colorectal cancer cell proliferation and migration via miR-141 (159) and miR-338-3p sponging (160), along with up-regulation of AIF (Allograft Inflammatory Factor 1) (152), and activation of transcription factor SLUG (45). In thyroid cancer, SNHG15 is a ceRNA for miR-510-5p (161) and miR-200a-3p (162).…”
Section: Small Nucleolar Rna Host Gene 15 (Snhg15)mentioning
confidence: 99%
“…Both univariate and multivariate analysis confirmed that SNHG15 expression was significantly associated with overall survival (OS) in CRC patients, suggesting that SNHG15 could be used as an independent prognostic factor and potential biomarker for CRC patients . Functional assays further demonstrated that knockdown of SNHG15 could inhibit CRC cell proliferation, activate cell apoptosis and suppress cell migration and invasion both in vitro and in vivo . Recently, SNHG15 has been shown to present a downside tendency on regulating miR‐141, which downregulates sirtuin 1 (SIRT1) in CRC cells.…”
Section: Expression Pattern Functions and Clinical Potentials Of Snhmentioning
confidence: 93%
“…LncRNA SNHG15 has been found in several studies to be dramatically upregulated in CRC tissues and cells . CRC patients with larger tumour size, advanced TNM stage and lymph node metastasis show higher SNHG15 expression . Furthermore, higher SNHG15 expression is correlated with a worse survival .…”
Section: Expression Pattern Functions and Clinical Potentials Of Snhmentioning
confidence: 99%
“…Several studies have shown the interaction of miR-141 with lncRNAs in different diseases including cancers (80,81,82). However, only few studies are available on lncRNAs and circRNAs that sponge miR-141 in CVD.…”
Section: Lncrnas and Circrnas That Sponge Mirna-141mentioning
confidence: 99%